The Use of Educational Games in Teaching Vocabulary: A Focus on EFL Young Learners (Journal of Academic Research, 2018)
Vocabulary acquisition is regarded as one of the difficult aspects in learning a target language. However, using games in teaching vocabulary can facilitate this task for teachers by creating more interesting environments for learners. Research has revealed that using games in vocabulary learning and teaching is beneficial because they improve students’ ability to memorize words, encourage students’ interaction, develop their communicative skills and enhance students’ motivation. This paper attempts to analyse the impact that language games have on EFL young learners, and how they affect their performance. The study was conducted in an English class of sixth grader students in Hassan Bin Thabet Elementary school, Misurata where English taught as a foreign language, and was guided by four questions: (1)What are the problems that encounter students in learning vocabulary? (2) What are the possible solutions for those problems? • How can games help in improving students' vocabulary? (4) How can teachers use games effectively in the classroom? In this study, data was collected from the participants (teachers and students) using interviews, pre-test and post-test as research instruments. The pre-test and post-test procedure was conducted for (25) EFL students, while (3) teachers were interviewed. Clearly, out of the findings of the comparison between the two tests before and after using games in teaching vocabulary, the researchers concluded that using games in class could improve students' performance positively.